Pengembangan Media Pembelajaran Virtual Reality Berbasis Android pada Pembelajaran Matematika SMP - Anggia Fernanda; Allen Marga Retta; Asnurul Isroqmi (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This development research aims to produce Android-based Virtual Reality learning media for mathematics learning that is valid, practical and effective. The development procedure uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Students at SMP Negeri 4 Tempilang Class VII 1 were the research subjects. The data collection techniques used were unstructured interviews, questionnaires, and student learning outcomes. This research uses descriptive data analysis on one variable, namely the quality of Android-based Virtual Reality learning media. The results of the research and data analysis obtained a questionnaire assessment from the three validators of 91.8% which was included in the very valid criteria, the average percentage of practicality was 90.7% which was included in the very practical criteria, and effectiveness was obtained at 82.6% which was included in the criteria very effective with 19 students who completed and 4 students who did not complete. Therefore, the researchers concluded that Android-based Virtual Reality learning media in junior high school mathematics learning has proven to be valid, practical and effective.